Role of Postoperative Patient-Reported Outcomes to Predict Ankle Arthroplasty and Arthrodesis Revision. (January 2020) - Desai, Sameer; Sutherland, Jason M.; Younger, Alastair; Penner, Murray; Veljkovic, Andrea; Yusuf, Fardowsa; Wing, Kevin
Background: Patient-reported outcomes are becoming common for measuring patient-centric outcomes in surgery. However, there is little known about the relationship between postoperatively collected patient-reported outcomes and objective clinical outcomes. The objective of this study was to measure whether postoperative Ankle Osteoarthritis Scale (AOS) values were associated with risk of revision among patients having ankle arthrodesis or total ankle arthroplasty for treatment of symptomatic end-stage ankle arthritis. Methods: This is a retrospective analysis of a longitudinal cohort of ankle arthrodesis and total ankle arthroplasty patients. A single center recruited patients between 2003 and 2013 and follow-up was at least 4 years. Patients completed the AOS preoperatively and annually following surgery. An extended Cox regression model incorporating time-varying AOS values was used to model risk of failure. A total of 336 patients and 348 ankles were included, representing 139 ankle arthrodesis procedures and 209 total ankle arthroplasties. Results: The median follow-up time for revisions was 8.2 years and 46 patients had a revision. Higher values of patients' AOS scores in the postoperative period were associated with a higher likelihood of revision (hazard ratio, 1.04 per 1-point increase; 95% confidence interval, 1.03-1.05). Ankle arthrodesis was associated with a reduced risk of revision compared with ankle fusion (hazard ratio, 0.12; 95% confidence interval, 0.03-0.49). Conclusion: This study showed that persistent pain and poor function after fusion or replacement surgery, as measured by elevated values of the AOS, were associated with higher risk of further surgery. Level of Evidence: Level III, retrospective cohort study.